Epidemiology of the 2010 Outbreak of Foot‐and‐Mouth Disease in Mongolia. Issue 5 (29th January 2014) - McFadden, A. M. J.; Tsedenkhuu, P.; Bold, B.; Purevsuren, B.; Bold, D.; Morris, R.
Summary Foot‐and‐mouth disease (FMD) occurred in five provinces and 24 counties as part of the FMD incursion into Mongolia during 2010. The first detection occurred on 21 April 2010 (confirmed 26 April 2010) with the last detection occurring approximately 8 months later on 13 December 2010. The number of livestock detected in the spring phase of the outbreak was 323 cattle and in the summer phase was 13 485 sheep, 6748 cattle, 5692 goats and 10 camels (total livestock summer phase = 25 935; for spring and summer phases combined = 26 258). Infection of livestock was confirmed by PCR for each affected county but not necessarily for every outbreak cluster involving more than one herder. It is likely that the summer phase of the outbreak was a continuation of the spring event. In the summer phase, the spatio‐temporal pattern of spread suggested an extension of infection from the main cluster in the Sukhbaatar county. There was also a number of long‐distance clusters established. The relative importance of spread by three potential pathways of gazelle, livestock, animal product and fomite movements has not been determined and will require further study. The estimated dissemination ratio (EDR) did not provide evidence of high rate of transmission of infection between herders; however, the data are limited by the quality of surveillance and the method of calculation which used the date of detection rather than the date of infection.